Gender Might Be Factor for Student Admission in Two Brazilian Medical Schools - Gabriel Henrique Beraldi; Julio Cesar Gagliardi Filho; Maria do Patrocinio Tenorio Nunes; Silmar Gannam (Revista Brasileira de Educação Médica)
This is a secondary data-based study conducted to investigate whether gender is related to acceptance. Two Brazilian Medical Schools, Universities A and B, were studied. Their entrance exams (EE) were analysed and the number of candidates who took the EE was compared to the number of students admitted to the MS according to gender, in the period between 1995 and 2009. The same data from MS in the United States in 2011 was also evaluated. There was an increase in the percentage of female applicants but it did not correspond to the percentage of admitted students of the same gender. There was a trend of selecting men. At A, 39.3% of the applicants and 47% of the admitted students were men (OR = 1.37; CI95% = 1.24 – 1.51). In B, men represented 39.3% of the applicants and 65.4% of the admitted students (OR = 2.93; CI 95% = 2.76 – 3.11). This was not seen in US MS. The analysis of the EE suggests that the greater selection of men could be a product of EE format.